PERUBAHAN NILAI BUDAYA MASYARAKAT CAP TIKUS DI DESA TALAITAD UTARA KECAMATAN SULUUN TARERAN KABUPATEN MINAHASA SELATAN - Liandry Vanny Lintong (HOLISTIK, Journal of Social and Culture, 2022)
Indonesia is a country with ethnic diversity. in the world. Each ethnic group has a different social, political, and cultural identity, such as different regional languages customs and traditions, belief systems and so on. Not only rich in culture, but also a country rich in natural resources both in the agricultural sector, fields, and marine products. In North Sulawesi, especially in Minahasa, it is famous for a liquor called "Cap Tikus". This liquor is made from the fermentation and distalation of juice from palm trees. Cap Tikus has become a drink that can be consumed supported by technology, this drink has an important role for the alcoholic beverage industry in Manado City, because it is a raw material for making liquor. Talaitad Village located in Suluun Tareran District, North Sulawesi Province is famous for (Cap Tikus to') or high alcohol content, even up to 80%. Cap tikus, which used to be used for sacred occasions, and other positive things, has now turned into an escape point. Uap tikus is a dangerous drink for health and causes crime when consumed excessively. Although dangerous, cap tikus has benefits when consumed according to the dose (not excessive). The results of Cap Tikus production are also the main source of income for farmers. Keywords: change of cultural values, alcohol, cap tikus